Draft Annual Plan 1986-87 Volume IV Rural Development (Special Programmes) Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
The Integrated Rural Development Programme is a centrally’ sore scheme which is being implemented in all the Development Blocks of the Division inclusive of LOC and Kargil Districts, The programme aims at providing direct assistance to the families falling below the poverty line. the assistance under the programme is being given at 33% and 25% to the small and marginal families. Accordingly a number of schemes are being incremented in the Blocks according to the felt needs of the families falling below poverty line and the assistance is being given to them in the shape of subsidy and loan from the various commercial banks.
Planning and Development Department Jammu and Kashmir Government